Defensive Driving bagi Awak Angkutan Barang Berbahaya untuk Peningkatan Keselamatan Transportasi Jalan - Rizaldy, Wynd; Lesmini, Lis (LPPM Universitas Bumigora, 2024)
The background of this community service is due to the need for knowledge of personnel working in the transportation and logistics as a manager, supervisor, driver and assistant driver related to the delivery of dangerous goods in accordance with national and international regulation. The purpose of this Community Service is to prevent incident during transporting the dangerous goods in accordance with the applicable regulations. This service activity is carried out on 13th May 2023 for member and non member of an National Logistic association namely National Logistic Community. The method used in the implementation of this service is by Webinar using a relaxed but focused conversation approach with online media zoom to the participants registered. The result of this service is the understanding of participant was 19%, an average increase from 78% to 97% obtained from pre and post tests of 15 participants from those National Logistic Community’s member.